Dataset of the complete genome of Streptomyces cavourensis strain 2BA6PGT isolated from sediment from the bottom of the salt lake Verkhnee Beloe (Buryatia, Russia) - Eric Tzyy Jiann Chong; De Chen Chiang; Keh Kheng Png; Elena Abidueva; Svetlana Zaitseva; Chenghang Sun; Ping-Chin Lee (Elsevier, 2022)
The Streptomyces cavourensis strain 2BA6PGT was isolated from sediment from the bottom of the salt lake Verkhnee Beloe (Buryatia, Russia). This strain’s 7,651,223 bp complete genome has a high G + C content of 72.1% and consists of 7,069 coding sequences and 315 subsystems. The 16S ribosomal RNA of isolate 2BA6PGT was most closely related to Streptomyces cavourensis strain NBRC 13026T (98.91% identity), followed by Streptomyces bacillaris strain ATCC 15855T (95.36%), Streptomyces rhizosphaericola strain 1AS2cT (94.68%), and Streptomyces pluricolorescens strain JCM 4602T (86.75%). These comparisons were supported by pairwise comparisons using average nucleotide identity (ANI) and DNA-DNA hybridization analysis. This is the first complete genome reported on Streptomyces cavourensis isolated from sediment from the bottom of the salt lake Verkhnee Beloe.